Foxo3a Regulates Apoptosis by Negatively Targeting miR-21 - Wang, Kun (American Society for Biochemistry and Molecular Biology, 2010)
MicroRNAs are a class of small non-coding RNAs and participate in the regulation of apoptotic program. Although miR-21 is able to inhibit apoptosis, its expression regulation and downstream targets remain to be fully elucidated. Here we report that the transcriptional factor Foxo3a initiates apoptosis by transcriptionally repressing miR-21 expression. Our results showed that doxorubicin could simultaneously induce the translocation of Foxo3a to the cell nuclei and a reduction in miR-21 expression. Knockdown of Foxo3a resulted in an elevation in miR-21 levels, whereas enforced expression of Foxo3a led to a decrease in miR-21 expression. In exploring the molecular mechanism by which Foxo3a regulates miR-21, we observed that Foxo3a bound to the promoter region of miR-21 and suppressed its promoter activity. These results indicate that Foxo3a can transcriptionally repress miR-21 expression. In searching for the downstream targets of miR-21 in apoptosis, we found that miR-21 suppressed the translation of Fas ligand (FasL), a pro-apoptotic factor. Furthermore, Foxo3a was able to up-regulate FasL expression through down-regulating miR-21. Our data suggest that Foxo3a negatively regulates miR-21 in initiating apoptosis.